Mengungkap Dampak Boikot Terhadap Nilai Pasar Perusahaan - Arum Pujiastuti (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The issuance of the Indonesian Ulema Council (MUI) Fatwa Number 83 of 2023 further supports the call for boycotting Israeli products as a show of solidarity with Palestinian fighters in Indonesia. This research explores the impact of the boycott on the market value of targeted companies by measuring the difference in abnormal returns and trading volume activity before and after the boycott. Employing a quantitative approach through an event study with paired sample t-tests and Wilcoxon signed-rank tests, this study examines seven targeted companies. The research findings indicate a significant negative abnormal difference before and after the boycott within a 3-day window. However, when extending the window to 5 and 10 days, the results show no significant differences in abnormal returns due to the boycott. Similar results are observed when examining the trading volume of stocks, which also did not exhibit significance.